ANALYSIS OF THE EFFECT OF SIDE OBSTACLES ON STALL DEA 2 ON THE PERFORMANCE OF JALAN AHMAD YANI, BARABAI CITY - Irshandy, Daffa Febri; Arsyad, Muhammad (CERUCUK, 2026)
Traffic flow density is very frequent on Jalan A. Yani, precisely during breakfast hours. The activity of several restaurants and the large number of buyers caused the parking load to be fully provided even to the point of using the shoulder of the road. So that this activity can affect the performance of the Jalan A Yani section in front of the Dea 2 stall and after the Dea 2 stall. This study aims to analyze traffic volume, speed, and density, as well as evaluate traffic performance on Jalan A Yani in front of Warung Dea 2 and after Warung Dea 2 and obtain the value of the service level index (ITP) and the influence of Warung Dea 2 on traffic performance on Jalan A Yani. The Greenshield model is one of the traffic flow characteristic relationship models where the linear relationship of speed and density is the relationship that is reviewed in the movement of traffic flow, considering the simplest function of the relationship so that it is easy to apply. Based on the results of the greenshield model research, it was found that the performance of the Jalan Ahmad Yani section of Barabai City in the area in front of Warung Dea 2 (there are side obstacles) has a maximum volume or capacity of 780,093 smp/h, a maximum speed of 38,416 km/h, and a maximum density of 30,962 smp/km and the performance of the Jalan Ahmad Yani section of Barabai City in the area in front of Warung Dea 2 in an area of 200 meters after Warung Dea 2 (no side obstacles) has a volume The maximum or capacity is 752,034 smp/h, the maximum speed is 47,007 km/h, and the maximum density is 18,469 smp/km. Side obstacles on the road body in the Warung Dea 2 area have an effect on increasing road capacity by 3.597%. However, the maximum speed decreased by 22.366% and the maximum density increased by 12.493% due to several side obstacle factors such as the density of pedestrian entry and exit activities, and the shoulder of the road being used as a parking lot in the Warung Dea 2 area which covered part of the lane on the road. Keywords:Density, Obstacles, Road Performance, Speed, and Traffic Peformance